Exploring the Relationship between Personal and Public Annotations - Marshall, Cathy; Brush, A.J. (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries (JCDL '04), 2004)
Today people typically read and annotate printed documents even if they are obtained from electronic sources like digital libraries. If there is a reason for them to share these personal annotations online, they must re-enter them. Given the advent of better computer support for reading and annotation, including tablet interfaces, will people ever share their personal digital ink annotations as is, or will they make substantial changes to them? What can we do to anticipate and support the transition from personal to public annotations? To investigate these questions, we performed a study to characterize and compare students’ personal annotations as they read assigned papers with those they shared with each other using an online system. By analyzing over 1,700 annotations, we confirmed three hypotheses: (1) only a small fraction of annotations made while reading are directly related to those shared in discussion; (2) some types of annotations – those that consist of anchors in the text coupled with margin notes – are more apt to be the basis of public commentary than other types of annotations; and (3) personal annotations undergo dramatic changes when they are shared in discussion, both in content and in how they are anchored to the source document. We then use these findings to explore ways to support the transition from personal to public annotations.